Risk of common infections in people with inflammatory bowel disease in primary care: a population-based cohort study - Peter M Irving; Simon de Lusignan; Kevin Barrett; Daniel Tang; Monica Nijher (BMJ Open Gastroenterology)
Objective To evaluate the risk of common infections in individuals with inflammatory bowel disease (IBD) [ulcerative colitis and Crohn’s disease] compared with matched controls in a contemporary UK primary care population.Design Matched cohort analysis (2014–2019) using the Royal College of General Practitioners Research and Surveillance Centre primary care database. Risk of common infections, viral infections and gastrointestinal infections (including a subset of culture-confirmed infections), and predictors of common infections, were evaluated using multivariable Cox proportional hazards models.Results 18 829 people with IBD were matched to 73 316 controls. People with IBD were more likely to present to primary care with a common infection over the study period (46% vs 37% of controls). Risks of common infections, viral infections and gastrointestinal infections (including stool culture-confirmed infections) were increased for people with ulcerative colitis and Crohn’s disease compared with matched controls (HR range 1.12–1.83, all p<0.001). Treatment with oral glucocorticoid therapy, immunotherapies and biologic therapy, but not with aminosalicylates, was associated with increased infection risk in people with IBD. Despite mild lymphopenia and neutropenia being more common in people with IBD (18.4% and 1.9%, respectively) than in controls (6.5% and 1.5%, respectively), these factors were not associated with significantly increased infection risk in people with IBD.Conclusion People with IBD are more likely to present with a wide range of common infections. Health professionals and people with IBD should remain vigilant for infections, particularly when using systemic corticosteroids, immunotherapies or biologic agents.Trial registration number Clinicaltrials.gov (NCT03836612).